Transcending transmission - Schoeneborn, Dennis; Trittin, Hannah (Corporate communications, 2013)
Purpose - Extant research on corporate social responsibility (CSR) communication primarily relies on a transmission model of communication that treats organizations and communication as distinct phenomena. This approach has been criticized for neglecting the formative role of communication in the emergence of organizations. This paper seeks to propose to reconceptualize CSR communication by drawing on the "communication constitutes organizations" (CCO) perspective.Design methodology approach - This is a conceptual paper that explores the implications of switching from an instrumental to a constitutive notion of communication.Findings - The study brings forth four main findings: from the CCO view, organizations are constituted by several, partly dissonant, and potentially contradictory communicative practices. From that viewpoint, the potential impact of CSR communication becomes a matter of connectivity of CSR to other practices of organizational communication. Communication practices that concern CSR should not be generally dismissed as mere "greenwashing" - given that some forms of talk can be action. Consequently, there is a need to investigate which specific speech acts create accountability and commitment in the context of CSR. The CCO view shows that CSR communication potentially extends the boundary of the organization through the involvement of third parties. Thus, it is fruitful to study CSR communication as a set of practices that aims at boundary maintenance and extension. Organizations are stabilized by various non-human entities that "act" on their behalf. Accordingly, CSR communication should also take into account non-human agency and responsibility.Originality value - This paper links the literature on CSR communication to broader debates in organizational communication studies and, in particular, to the CCO perspective. By applying the CCO view, it reconceptualizes CSR communication as a complex process of meaning negotiation.